The effect of ESG rating on ETF performance: Evidence from different market conditions - Piiroinen, Joel (My University, 2025)
In recent decades, the financial world has undergone a change, with the rise of exchange-traded funds (ETFs) as cost-effective and diversified investment vehicles and the integration of environmental, social and governance (ESG) factors into investment decision-making. The rise of these reflects investors' growing demand for both efficiency and responsibility, making the interplay between ESG considerations and ETF performance an important area in modern financial research. This thesis investigates the effect of ESG ratings on the financial performance of equity ETFs across three different market conditions: a stable period (February 2016 – February 2018), the high-volatility COVID-19 pandemic (February 2020 – February 2022), and the period following the Russian invasion of Ukraine (February 2022 – February 2024). Utilizing portfolio performance analysis with Jensen's alpha and Sharpe ratio, and a multivariate regression model controlling for fund-specific characteristics, the research provides detailed insights into the effects of ESG integration. The findings reveal that during the stable period there is a negative correlation between ESG ratings and ETF performance, although, when controlling for fund-specific characteristics, ESG ratings show a non-linear inverted U-shaped effect on ETF performance. During the COVID-19 pandemic, the ESG rating of an ETF did not show a statistically significant linear effect on performance; however, a non-linear inverted U-shaped relationship emerges in the multivariate analysis, suggesting that moderate ESG scores might have been beneficial. During the Russian invasion of Ukraine, a statistically significant positive correlation between ESG ratings and ETF performance is observed, although this relationship also exhibits an inverted U-shape. This indicates that while ESG generally contributed positively to performance during this geopolitical and energy crisis, benefits might peak at certain ESG levels. Overall, the study concludes that the impact of ESG ratings on ETF performance can depend on the prevailing market conditions and the specific nature of the crisis.

Viime vuosikymmeninä rahoitusmaailma on muuttunut, kun pörssinoteeratut rahastot (ETF) ovat nousseet kustannustehokkaina ja monipuolisina sijoitusvälineinä, ja samaan aikaan ympäristöön, yhteiskuntavastuuseen ja hallintotapaan (ESG) liittyvät tekijät on otettu huomioon sijoituksiin liittyvässä päätöksenteossa. Näiden yleistyminen heijastaa sijoittajien kasvavaa vaatimusta sekä tehokkuudesta että vastuullisuudesta, minkä vuoksi ESG:n ja ETF:ien suorituskyvyn välinen vuorovaikutus on nykyaikaisen rahoitustutkimuksen tärkeä osa-alue. Tässä tutkielmassa tutkitaan ESG-luokitusten vaikutusta osake-ETF:ien suorituskykyyn kolmessa eri markkinaolosuhteessa: vakaa ajanjakso (helmikuu 2016 - helmikuu 2018), korkean volatiliteetin COVID-19-pandemia (helmikuu 2020 - helmikuu 2022) ja Venäjän hyökkäystä Ukrainaan seuraava ajanjakso (helmikuu 2022 - helmikuu 2024). Tutkimus tarjoaa tietoa ESG-integraation vaikutuksista analysoimalla salkun suorituskykyä Jensenin alfan ja Sharpen luvun sekä monimuuttujaisen regressiomallin avulla, jolla kontrolloidaan rahastokohtaisia ominaisuuksia. Tuloksista käy ilmi, että vakaana ajanjaksona ESG-luokitusten ja ETF:ien tuoton välillä on negatiivinen korrelaatio, vaikka rahastokohtaisten ominaisuuksien kontrolloinnin yhteydessä ESG-luokituksilla on epälineaarinen käänteisen U:n muotoinen vaikutus ETF:ien tuottoon. COVID-19-pandemian aikana ETF:n ESG-luokituksella ei ole tilastollisesti merkittävää lineaarista vaikutusta tuottoon, mutta monimuuttuja-analyysissä ilmenee epälineaarinen käänteisen U:n muotoinen suhde, mikä viittaa siihen, että maltilliset ESG-luokitukset ovat saattaneet olla hyödyllisiä. Venäjän hyökkäyksen aikana Ukrainaan havaitaan tilastollisesti merkitsevä positiivinen korrelaatio ESG-luokitusten ja ETF:ien tuoton välillä, vaikka tämäkin suhde on käänteisen U:n muotoinen. Tämä viittaa siihen, että vaikka ESG vaikutti yleisesti ottaen myönteisesti suorituskykyyn tässä geopoliittisessa ja energiakriisissä, hyödyt saattoivat saavuttaa huippunsa tietyillä ESG-luokituksilla. Kaiken kaikkiaan tutkimuksessa todetaan, että ESG-luokitusten vaikutus ETF:n tuottoon voi riippua vallitsevista markkinaolosuhteista ja kriisin luonteesta.
Keywords: pörssinoteeratut rahastot; vastuullinen sijoittaminen; COVID-19; Venäjän hyökkäys Ukrainaan 2022; arvopaperimarkkinat; portfoliot; arvopaperisalkut; tuotto; volatiliteetti; fi=Laskentatoimi ja rahoitus|en=Accounting and Finance|; Master's Degree Programme in Finance